2012
DOI: 10.1136/jmedgenet-2012-101251
|View full text |Cite
|
Sign up to set email alerts
|

TheDYRK1Agene is a cause of syndromic intellectual disability with severe microcephaly and epilepsy

Abstract: The identification of a truncating mutation in a patient with ID, severe microcephaly, epilepsy, and growth retardation, combined with its dual function in regulating the neural proliferation/neuronal differentiation, adds DYRK1A to the list of genes responsible for such a phenotype. ID, microcephaly, epilepsy, and language delay are the more specific features associated with DYRK1A abnormalities. DYRK1A studies should be discussed in patients presenting such a phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 32 publications
3
106
2
2
Order By: Relevance
“…There were some strikingly similar features between members of our cohort and the features of previously reported individuals with a similar genotype, [10][11][12][13][14][15][16][17] indicating that this is a recognizable syndrome. Microcephaly, IUGR, brain abnormalities consistent with cerebral hypomyelination, global DD, ID, severe speech delay, seizures, broadbased gait, short stature, minor skeletal anomalies, and distinct facial gestalt were the most commonly shared features.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…There were some strikingly similar features between members of our cohort and the features of previously reported individuals with a similar genotype, [10][11][12][13][14][15][16][17] indicating that this is a recognizable syndrome. Microcephaly, IUGR, brain abnormalities consistent with cerebral hypomyelination, global DD, ID, severe speech delay, seizures, broadbased gait, short stature, minor skeletal anomalies, and distinct facial gestalt were the most commonly shared features.…”
Section: Resultssupporting
confidence: 84%
“…[10][11][12][13][14][15][16] These are included in Supplementary Table S1. Specific evidence supporting the role of DYRK1A individuals includes the deletion of the non-coding 5′-UTR (NM_130436.3) in one published case, 11 as well as the disruption of DYRK1A by translocation in two cases reported by Moller et al 10 Furthermore, in the Database of Genomic Variants, there are only two self-reported phenotypically normal individuals with exonic losses of DYRK1A (8 Kb and 181 Kb). There are no segmental duplications flanking the deletion breakpoints.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports indicated that 21q22 micro deletions including only DYRK1A (dual-specificity tyrosine-(Y)-phosphorylation-regulated kinase 1A) gene was found in patients presented with microcephaly, growth retardation, epilepsy, delayed speech and similar features such as low set ears, long philtrum, micrognathia [4,14,23]. Deletion including the 5` region of the DYRK1A gene was observed in another patient with microcephaly, seizures and dysmorphic features [24]. It was suggested that the DYRK1A gene might be the causative gene responsible for most of the clinical features observed in interstitial deletion of chromosome 21.…”
Section: Discussionmentioning
confidence: 99%